Sliding mode control of wind energy conversion systems: Trends and applications. (October 2022) - Mousavi, Yashar; Bevan, Geraint; Kucukdemiral, Ibrahim Beklan; Fekih, Afef
Abstract: Motivated by the increasing concerns over environmental challenges such as global warming and exhaustion of fossil-fuel reserves, the renewable energy industry has become the most sought-after source of electrical energy production worldwide. In this context, wind energy conversion systems (WECS) are one of the most dominant and fastest-growing technologies, playing an increasingly vital role in renewable power generation. To meet this growing demand and mitigate the vulnerability of WECS to various sets of internal/external faults, the cost-effectiveness and efficient power production of WECS must be ensured, which highlights the critical role of the control system. This topic has been intensively studied in the literature, and many control approaches have been developed to deal with the simultaneous enhancement of efficiency and reliability of WECS. However, sliding mode control (SMC) has proved its reliable and superior performance among most control strategies due to its inherent robustness to parametric uncertainties and disturbances and ease of design and implementation. Accordingly, this paper provides a comprehensive survey of existing literature on the application of SMC and its emerging modifications to address different control design problems for WECS. Highlights: An explicit modeling of wind energy conversion systems (WECS). A comprehensive survey of existing literature on SMC designs for WECS. A survey of the different variants of SMC designs for WECS. A review of existing chattering mitigation techniques in SMC designs for WECS.